(untitled) (International Journal of Banking and Finance, 2003)
This paper attempts to fill a void in the finance literature by reporting the reliability of theoretical valuation models against the market values of banking corporations. The dividend, operating cash flows and the free cash flow valuation approaches are operationalised to estimate fair values of banks. These values are then compared with market values. This results, using the Theil’s U-coefficient, show that the operating cash flow approach provides estimates that are better than the naïve model estimates. The other two approaches produced results no better than the naïve model. A probable reason for the poor performance of the free cash flow approach is suggested. Outsider’s estimation of investment values needed for free cash flow calculation is likely to introduce serious errors irrespective of the theoretical bases of models widely used in the industry.